PERBANDINGAN DURASI PEKERJAAN BOR KERING DAN BOR BASAH PADA PEKERJAAN TIANG BOR DI PROYEK X - Florencio, Ricardo; Irfanto, Ryobi; Wijaya, Usman (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2024)
The duration of construction work is a crucial factor that affects the efficiency and success of a project, especially in bored pile construction. The purpose of this study is to identify the differences in the duration of dry and wet drilling work along with internal and external factors that affect the duration. Dry drilling is a drilling condition without using fluid, while wet drilling is a drilling condition using polymers or fluids to maintain the soil wall so that it does not collapse. The study was conducted through unstructured interviews and field observations by finding 40 data on project X. Data processing in this study was carried out using a comparative method and presented in the form of tables and graphs. Based on this comparison, it can be seen which work is more efficient and faster and the factors that influence it. Based on data analysis, the dry drilling method is more efficient with a total working duration of 3.26 hours compared to 6.37 hours required for wet drilling. The biggest difference is in the drilling and cleaning time which is different by 2.52 hours. In addition, factors such as tool damage, bad weather, and technical difficulties can affect the duration of work, especially when using wet drilling. This study provides important information for choosing the right drilling method to reduce working time and increase project efficiency